2022
DOI: 10.1186/s10020-022-00497-2
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system effects of 5-HT7 receptors: a potential target for neurodegenerative diseases

Abstract: Abstract5-HT7 receptors (5-HT7R) are the most recently identified among the family of serotonin receptors. Their role in health and disease, particularly as mediators of, and druggable targets for, neurodegenerative diseases, is incompletely understood. Unlike other serotonin receptors, for which abundant preclinical and clinical data evaluating their effect on neurodegenerative conditions exist, the available information on the role of the 5-HT7R receptor is limited. In this review, we describe the signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 119 publications
0
4
0
Order By: Relevance
“…Moreover, it has been shown that the 5-HT 7 receptor is associated with macrophage M2 polarization, characterized as protective cells in an inflammatory context [ 20 ]. A recent review describes the known protective roles of 5-HT 7 receptors in neurodegenerative diseases that are associated with reduction of oxidative stress, synaptic remodeling, and immunomodulation [ 32 ]. All these reports support our results and the 5-HT 7 receptor ability to modulate immune function in MS and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that the 5-HT 7 receptor is associated with macrophage M2 polarization, characterized as protective cells in an inflammatory context [ 20 ]. A recent review describes the known protective roles of 5-HT 7 receptors in neurodegenerative diseases that are associated with reduction of oxidative stress, synaptic remodeling, and immunomodulation [ 32 ]. All these reports support our results and the 5-HT 7 receptor ability to modulate immune function in MS and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT6 receptors are postsynaptic GPCRs located in the corpus striatum, nucleus accumbens, cerebral cortex, amygdala, hippocampus, and hypothalamus ( Figure 2 ) (Quintero-Villegas and Valdés-Ferrer, 2022 ). Recent studies have demonstrated the antidepressant and anxiolytic effects of two specific 5-HT6 receptor agonists in rodents (Carr et al, 2011 ).…”
Section: Serotonin and Its Receptorsmentioning
confidence: 99%
“…In addition, a recent study revealed that BDNF and the 5-HT7 receptor also interconnect. Indeed, when activated, these receptors increase the level of BDNF and TrkB affinity [ 100 ]. Interestingly, a study in rodents demonstrated that a single injection of BDNF improved the activity of serotonin transporter in the hippocampus of these animals.…”
Section: Exploring Bdnf and Its Connection To Mood Disordersmentioning
confidence: 99%